Energy-Water Nexus in Southern Africa : Background Paper to Support Dialogue in the Region - World Bank (Washington, DC, 2016)
The objective of this paper is to provide high-level background information on the interdependency between the supply of electricity and water in Southern Africa. The paper assimilates information based an extensive review of recent work on the energy and watersectors in the region and beyond, and the World Bank’s sector dialogue in the region. The paper is intended to help facilitate a dialogue on the energy-water nexus in the region, especially fromthe perspective of electricity sector planning, and help the World Bank engage key sectorstakeholders on the issue.The value of this paper is in bringing together the latest knowledge work and other key information relevant for energy-water nexus dialogue in Southern Africa. This information has been derived from a number of fragmented sources, and an effort has been made to present the information in a logical framework, in one document that can help initiate discussions in the region.This paper was conceptualized as a background discussion paper and does not seek to make any recommendations on policy alternatives to tackle challenges facing the region on energy-water nexus issues. Any recommendations should be rooted in a thorough assessment of the specificchallenges, institutions and objectives of the region; and most importantly should follow from aconstructive regional dialogue amongst key stakeholders.The issues and implications that surround the energy-water nexus are numerous. The use of electricity and water as critical inputs to economic activity, implies that there are many interlinkages that can be explored. To increase the usefulness of the information and the framework presented, this paper focuses on the perspective of electricity supply, and highlights nexus issues that are directly relevant to it. Important related nexus issues such as agriculture and its dependence on reliable water and electricity (the energy-water-food nexus) are not considered and are left for future work. Thus, in referring to the energy–water nexus, the paper considers issues on electricity and water sectors in relation to electricity supply and long-term planning around it, including the feedback loop to water. By highlighting key analytical work and drawing insights relevant to Southern Africa, this paper aims to support an informed regional dialogue on decision making about the energy–water nexus in the region.